2015
DOI: 10.1038/srep15028
|View full text |Cite
|
Sign up to set email alerts
|

A simple bridging flocculation assay for rapid, sensitive and stringent detection of gene specific DNA methylation

Abstract: The challenge of bringing DNA methylation biomarkers into clinic is the lack of simple methodologies as most current assays have been developed for research purposes. To address the limitations of current methods, we describe herein a novel methyl-protein domain (MBD) enrichment protocol for simple yet rapid and highly stringent selection of highly methylated DNA from limiting input samples. We then coupled this with a DNA-mediated flocculation assay for rapid and low cost naked-eye binary evaluation of highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…These data was much better than our previous gold-DNA based approach (Koo et al 2014a;Sina et al 2014) and was of comparable to recent approaches Koo et al, 2014b;Wang et al, 2016;Wee et al, 2015a;Wee et al, 2015b), and clearly demonstrate that our approach is both specific and sensitive in detecting methylated DNA in the nanogram regime.…”
Section: Principlementioning
confidence: 58%
See 2 more Smart Citations
“…These data was much better than our previous gold-DNA based approach (Koo et al 2014a;Sina et al 2014) and was of comparable to recent approaches Koo et al, 2014b;Wang et al, 2016;Wee et al, 2015a;Wee et al, 2015b), and clearly demonstrate that our approach is both specific and sensitive in detecting methylated DNA in the nanogram regime.…”
Section: Principlementioning
confidence: 58%
“…While all these methods have many advantages, their sensor fabrication procedure and data deconvolution methods are rather complicated due to the involvement of complex surface functionalisation steps or coupling chemistry Kato et al, 2011;Kato et al, 2008;Koo et al, 2014b;Kurita et al, 2012;Taleat et al, 2015;Wang et al, 2016;Wee et al, 2015a;Wee et al, 2015b;Zhang et al, 2015). Therefore, a simple and inexpensive method that could simplify the detection method by avoiding the complicated chemistry underlying each step of the sensor fabrication represents an appealing alternative to alleviate some of these issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have used affinity agents, such as antibodies or methyl‐CpG‐binding domain (MBD) proteins, to distinguish methylated and unmethylated CpG dinucleotides without requiring chemical conversion. Many of these methods use affinity agents to enrich for densely methylated regions of the genome prior to sequencing or analysis via microarray, and more recently, MBD capture techniques have been used with isothermal recombinase polymerase amplification in a bridging flocculation assay for a simple and sensitive readout method …”
Section: Introductionmentioning
confidence: 99%
“…13 Ikeda et al reported peptide-based hydrogels that have the ability to encapsulate enzymes and detect small molecules including glucose, lactose and sarcosine. 14 However, these and other approaches 15,16 all relied only on visual monitoring of the output signals. On the other hand, a great variety of elcrosensors including smartphone-based, RGB-Depth, electromagnetic and others, have been developed for visually impaired people.…”
mentioning
confidence: 99%